Space-fed Array Variations of E-shape and U-slot cut Rectangular Microstrip Antennas using Modified Feed for Gain Enhancement - Amit A. Deshmukh; Adil Parvez; Venkata A. P. Chavali (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract Space-fed array comprising of E-shape or U-slot cut rectangular microstrip antennas using the modified feed designs are proposed for higher gain and wider bandwidth. Modified feed optimally illuminates the edge space-fed elements to achieve a maximum gain. Amongst the two space-fed array variations, 7 x 7 E-shape space-fed array, excited using the feed comprising of gap-coupled and stacked E-shape patches provides bandwidth and gain of 2.085 GHz (48.97%) and 18.5 dBi, respectively. The antenna exhibits broadside radiation pattern across the complete bandwidth. An experimental validation has been carried out for the simulated results that show a close agreement.